Faith in Politics - Reichley, James (Book collections on Project MUSE., 2002)
"According to current polls, about 85 percent of Americans identify with some religious faith and more than 40 percent say they attend religious services at least once a week. In recent years, religious observance - and even religious belief - have become important factors influencing voter choice. Active participation in electoral politics by some religious groups has fueled apprehensions that the traditional separation of church and state may be threatened." "In Faith in Politics, Reichley explores the history of religion in American public life and considers some practical and philosophic questions affecting future participation by religious groups in the formation of public policy." "Reichley begins by examining the various attitudes and points of view of strict separationists, liberal social activists, moderate accommodationists, and direct interventionists. He goes on to discuss the way religion and politics relate to each other through a theoretic structure of seven value systems: monism, absolutism, ecstasism, egoism, collectivism, civil humanism, and transcendental idealism."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.